Analisis Perdagangan Bilateral Indonesia Indonesia dengan Malaysia Periode 2003-2012 - Maulana, Iskandar; Putro, Tri Sukirno; ', Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine (bilateral) development and comparison of trade between the two countries, Indonesia and Malaysia for the period 2003 to 2012 As this study shows the shape of trade, and the indicators that affect trade between Indonesia and Malaysia. The data used are secondary data obtained from the BPS (Central Bureau of Statistics) and the World